Calibration of rising plate meter in prairie kikuyo grass (Pennisetum Clandestinum Hochst.Ex Chiov) in the high colombian tropics - Moreno, Diego; Fonseca, Carolina; Rodríguez-Molano, Carlos Eduardo; Pulido-Suarez, Néstor Julián (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Colombian Andean region, in the department of Boyacá at 2,560 meters above sea level in the Colombian dairy belt, livestock farms are characterized by the predominant perennial forage species known as Kikuyo (Pennisetum clandestinum Hochst.ex Chiov), a stoloniferous growth grass. The objective of this study was to obtain the linear regression equation for the proper calibration of the forage dish in order to predict the availability of dry matter per hectare. This investigation was carried out in the course of 2014, (from March to December); for this investigation, measurements were taken with a Forage Plate in 21 cattle farms belonging to the Alto Chicamocha region. A total of four hundred (400) samples were taken during the dry and rainy seasons. The formula was developed by means of a mathematical method of simple linear regression, relating the compressed height of the forage and the actual availability of dry matter obtained by cutting and subsequent drying. %. According to the formula it was determined that for each unit of measurement of the forage dish, the total phytomass availability was increased in 259.42 kg of Dry Matter (MS) and an intercept of 2978.92 was obtained. These results lead to the use of the equation as an alternative to calculate dry matter available throughout the year in Kikuyo grasslands. The resulting equation for the calibration of the Forage Plate in Kikuyo grasslands (Pennisetum clandestinum) was Kg Ms / Ha = 259.42x + 2978.9 where the height compressed by the forage dish was replaced and with a coefficient of determination (R2) of 77.67%.